Development of AA6082 based metal matrix composite using Sic, Ti, Ni, Cr by conventional casting technique. (2021) - Mohanraj, C.; kumar, K.M. Naveen; PraveenKumar, K.; Mukesh, S.
Abstract: This paper is focused to develop the AA6082 based metal matrix composite using SiC, Ti, Ni and Cr by conventional casting methods for aviation applications. To attain the better properties like high entropy alloys, the maximum values of proportions are set during casting. The proportions of each matrix components include 3 wt%, 5 wt% and 7 wt%. The fabricated samples were subjected to mechanical and metallurgical testing and results indicates that the hardness with 5 wt% was increased upto 22.3 RHN, 13.33 RHN 3.6 RHN the base metal, 3 wt% and 7 wt%. The tensile strength improved upto 120 MPA, 11 MPA, 13 MPA than the base metal, 3 wt% and 7 wt%. Also the uniform stirring was done by electric motor stirrer; this leads the uniform dispersion of all the matrix components throughout the samples. The scanning electron microscope (SEM) images indicated that better layer formation found with sample 2 in terms of resist to pealing when it loaded.